Wave Field Propagation in Extended Highly Anisotropic Media. Issue 7 (22nd July 2019) - Rino, Charles; Carrano, Charles; Groves, Keith
Abstract: The theory propagation in the Earth's ionosphere is well established. However, with the advent of Global Navigation Satellite System measurements, new demands are being placed on satellite system performance evaluation and diagnostic measurements. Propagation simulations are essential for system performance evaluation and they provide guidelines for interpreting diagnostic measurements. This paper presents simulations of propagation in extended highly anisotropic media obtained with split‐step integration of the parabolic wave equation. This requires three‐dimensional realizations of the electron density structure. A new configuration‐space model is used to generate realizations as summations of striations, which are local to field lines with defined scales and peak densities. The scale and peak densities can be selected to generate specified power law spectral density functions. An analytic three‐dimensional expectation spectral density function provides a parameterized ionospheric structure model. The simulations results show that replacing the extended structure with an equivalent phase screen placed at the center of the structured region provides statistically equivalent realizations of observation‐plane measurements at propagation distances greater than the layer extent. The equivalence is independent of the propagation direction relative to the magnetic field direction, although there is some variation for the extreme propagation disturbances caused by field‐aligned propagation. We also investigate the interpretation of in situ and path‐integrated diagnostic measurements and two‐dimensional propagation models, which are being used to model diagnostic measurements directly. Key Points: Propagation in extended anisotropic media has become important with the advent of global navigation satellites New configuration‐space models are well suited for simulations An equivalent phase‐screen model captures the structure and provides guidelines interpreting diagnostic measurements